Coping with food poverty in cities : the case of urban agriculture in Glen Norah Township in Harare. - Masvaure, Steven. (2013)
Urban agriculture is a common and permanent phenomenon across most African cities. The general trend in urban agriculture is that it is more pronounced among the poor urban households. Poor households often spend more than 60% of their income on food alone. It acts as coping mechanisms to urban poverty. The traditional view of urban agriculture is that it is a temporal activity which has no place in cities. These traditional views emerge from development policies which tried to tailor African countries’ economic development to follow western economic development models. The fact that urban agriculture has been prevalent in African cities before the advent of colonialism shows that instead of viewing it as temporal activity a socio-historical and socio-economic analysis of urban agriculture is necessary to understand the socio-economic mechanisms behind it. The major thrust of this research was to understand the logic behind practising farming in cities. Urban agriculture in this thesis is presented from urban farmers’ perspective. Using data collected and the literature review for this thesis I developed the Urban Livelihoods Coping Model (ULCM). This model acknowledges the fact that the socio-economic conditions and the socio-historical context of Zimbabwe was as a result of the influence of ‘western leaning’ development policies influenced by theoretical framework of modernisation and associated theories. A combination of these theories with cultural factors and the impact of Structural Adjustment Policies resulted in the present situation where urban agriculture plays a critical in the survival of the urban poor as a coping mechanism. The ULCM ascribes the emergence of urban agriculture to necessity, ability and opportunity. Necessity for food emanates from insufficient incomes to purchase food in cities. The ability comes in the form of farming skills transferred from the rural areas to urban areas as households migrate. Opportunity comes in the form of availability of land for cultivation. Increase in poverty in cities will subsequently result in an increase in urban agriculture. It is apparent that without urban agriculture in Glen Norah most of the families will find it difficult to survive. The significance of this study is that it will help in the socio-economic understanding of urban agriculture and how it can be factored into urban planning systems. === Thesis (M.Soc.Sc.)-University of KwaZulu-Natal, Durban, 2013.